Hepatocyte Transplantation: Cell Sheet Technology for Liver Cell Transplantation - Tatsumi, Kohei (Curr Transplant Rep, 2017)
PURPOSE OF REVIEW: We will review the recent developments of cell sheet technology as a feasible tissue engineering approach. Specifically, we will focus on the technological advancement for engineering functional liver tissue using cell sheet technology, and the associated therapeutic effect of cell sheets for liver diseases, highlighting hemophilia. RECENT FINDINGS: Cell-based therapies using hepatocytes have recently been explored as a new therapeutic modality for patients with many forms of liver disease. We have developed a cell sheet technology, which allows cells to be harvested in a monolithic layer format. We have succeeded in fabricating functional liver tissues in mice by stacking the cell sheets composed of primary hepatocytes. As a curative measure for hemophilia, we have also succeeded in treating hemophilia mice by transplanting of cells sheets composed of genetically modified autologous cells. SUMMARY: Tissue engineering using cell sheet technology provides the opportunity to create new therapeutic options for patients with various types of liver diseases.